The challenge of Nigeria's indigenization - Sanda, Akinade Olumuyiwa (Ibadan : Nigerian Institute of Social and Economic Research, 1982)
This book examines the indigenization policy in Nigeria with particular references to the decree, industrial panel, self reliance among others.
Includes bibliographical references: p. 126-130.
lje 17/01/2018
Loans
Keywords: Africanization; Nigeria